Development of a Smart Sniffer Device for the Detection of Illicit Drugs, Homemade Explosives, and their Precursor Chemicals - Hardy, Iona (Cranfield University, 2020)
The controlled drug market in the UK alone is worth £9.4 billion a year (£19 billion a year cost to society) and is used to finance other crimes, including terrorism with enormous social-economical costs. The threat continues to change and exploitation of the latest scientific and technical advances to enhance operation capabilities for an early detection of terrorist and criminal activities, is at the core of Law Enforcement Agencies (LEAs) operational requirements. Among the detection technologies currently used/explored by UK and International market, a portable sniffer device that can detect multiple illicit substances, in a non-destructive, rapid, and accurate manner, would offer a valid alternative to LEAs.The CRIM-TRACK sniffer device was developed by Cranfield and Danish Technical University (EU FP7 project) and is currently at TRL 4. See attached file for the full abstract.
Keywords: 'DSDS20 Poster'; 'DSDS20'; 'CRIM-TRACK sniffer system'; 'Drugs detection'; 'NMR characterisation'; 'NMR Spectroscopy'